ORAL HISTORY: AN ALTERNATIVE OF ISLAMIC HISTORIOGRAPHY IN BOLAANG MONGONDOW - Imam Mashud (Aqlam: Journal of Islam and Plurality, 2023)
Abstract: Today's Islamic historiography in Bolaang Mongondow, North Sulawesi, has not been thoroughly investigated in order to show the existence of Islamic history in Bolaang Mongondow. The lack of written sources in developing Islamic historiography is one of the challenges recognized by Islamic historiography. The majority of Islamic historiography in Bolaang Mongondow continues to employ colonial material as a primary basis to construct how Islamic history is told. Nevertheless, the legitimacy of colonial data/historiography must still be questioned. Furthermore, the reconstruction of Islamic Historiography in Bolaang Mongondow can be described as unmoved, with the historical narrative limited to discussions based solely on written sources. Oral history is offered as an alternative to exploring Islamic history through interviews. As a consequence, Islamic historiography, particularly in the Bolaang Mongondow region, will present an innovative interpretation of Indonesian-centric Islamic historiography by emphasizing the roles of ordinary citizens rather than notable figures in its historical story. Key Words : Historical Approach, Oral Method, Decolonization Abstrak: Historiografi Islam di Bolaang Mongondow Sulawesi Utara saat ini masih belum massive digali untuk menampilkan jejak Sejarah Islam di Bolaang Mongondow. Salah satu permasalahan Historiografi Islam yang dihadapi adalah kurangnya sumber-sumber tertulis dalam Menyusun historiografi Islam tersebut. Sebagian besar historiografi Islam di Bolaang Mongondow masih bergantung data kolonial sebagai sumber primer untuk menyusun bagaimana Sejarah Islam di narasikan. Padahal data/historiografi kolonial masih perlu dikritisi dan pertanyakan kembali keabsahannya. Akhirnya rekonstruksi Historiografi Islam di Bolaang Mongondow bisa dikatakan stagnan dengan narasi Sejarah yang terbatas pada pembahasan-pembahasan yang memiliki data tertulis saja. Sejarah lisan hadir sebagai alternative untuk menggali Sejarah Islam dengan metode wawancaranya. Hasilnya Historiografi Islam khusunya di wilayah Bolaang Mongondow akan menampakan wajah baru mengenai Historiografi Islam yang Indonesia sentris dengan menampilkan peran orang biasa daripada peran-peran orang besar dalam narasi sejarahnya.  Kata Kunci : Pendekatan Sejarah, Metode Lisan, Dekolonisasi